Comparative Analysis of "Nature of Interpretation by Qur’an Judgment" from Shia and Sunni Commentators' Perspective - Esfahani, Seyyed Abdullah; Hosseini, Seyyede Masoome (Journal of History Culture and Art Research, 2017)
The intellectual and religious prohibition and indecency of the "interpretation by Quranic judgment" is agreed by the Shia and Sunni commentators and the scholars of Qur’an, though the reason behind the different attitude is in their perspectives' "basics, sources and rules of interpretation" in the assertion of diverse "nature of interpretation by judgment". The main question posed in this paper developed by descriptive analytical-systematic method is to comparatively contrast the Shia and Sunni commentators regarding the nature of interpretation by Quranic judgment, suggesting the comprehensive principle and integrity of Folk of Household's view in this respect.